2020
DOI: 10.1136/archdischild-2020-320549
|View full text |Cite|
|
Sign up to set email alerts
|

New screening approach to detecting congenital syphilis in China: a retrospective cohort study

Abstract: BackgroundDiagnosis of congenital syphilis (CS) is not straightforward and can be challenging. This study aimed to evaluate the validity of an algorithm using timing of maternal antisyphilis treatment and titres of non-treponemal antibody as predictors of CS.MethodsConfirmed CS cases and those where CS was excluded were obtained from the Guangzhou Prevention of Mother-to-Child Transmission of syphilis programme between 2011 and 2019. We calculated sensitivity, specificity, positive predictive value (PPV) and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…A retrospective study in China concluded that maternal nontreponemal titres preceding treatment and timing of treatment in pregnancy can be surrogate indicators in diagnozing congenital syphilis. This study found that nontreponemal titres exceeding 1 : 8 had the highest positive predictive value for congenital syphilis (37.3%) compared with maternal treatment after 28 weeks [53 ▪ ].…”
Section: Of the Infantmentioning
confidence: 61%
See 1 more Smart Citation
“…A retrospective study in China concluded that maternal nontreponemal titres preceding treatment and timing of treatment in pregnancy can be surrogate indicators in diagnozing congenital syphilis. This study found that nontreponemal titres exceeding 1 : 8 had the highest positive predictive value for congenital syphilis (37.3%) compared with maternal treatment after 28 weeks [53 ▪ ].…”
Section: Of the Infantmentioning
confidence: 61%
“…The diagnosis of congenital syphilis can be complex, particularly given the majority of infected infants are asymptomatic at birth. Factors that need to be considered for a diagnosis of congenital syphilis include maternal treatment history, maternal and infant serology, histological and microbiological testing of the placenta, physical examination of the infant and appropriate imaging of the infant [34,48,53 ▪ ] (Table 2). Clinical assessment involves evaluating adequacy of maternal treatment, examination of the newborn (for rash, hepatomegaly, rhinitis, lymphadenopathy), ophthalmology examination, chest and long bone radiographs, neuroimaging and audiology [2,54] (Fig.…”
Section: Of the Infantmentioning
confidence: 99%
“…This finding is comparable to the national data while very low compared with nearing Asian countries. 11 , 15 As the published report CDC USA showed a random increase of syphilis cases. 16 According to Cohen MS and his co-worker, China was declared a syphilis-free country until the really 1980s, but after the economic reform was introduced, cases now reported in some areas.…”
Section: Discussionmentioning
confidence: 99%
“…TRUST is used as a type of effective screening strategy in detecting the severity of syphilis [ 13 ] and as an auxiliary surrogate indicator for the diagnosis of congenital syphilis in China. [ 14 ] Serum TRUST titer of the patients before the initial treatment and in the month before delivery, as well as of their newborn babies at birth, were tested routinely and recorded. The diagnosis of congenital syphilis in newborns requires both TPPA and T. pallidum immunoglobulin M test result positive.…”
Section: Methodsmentioning
confidence: 99%